In Search for (Non)New Instruments to Support the Employment of Deafblind People - Kasprzak, Tomasz (Niepełnosprawność i praca: Wymiary, konteksty, perspektywy, 2024)
The professional situation of individuals with simultaneous hearing and visual impairments is a topic reluctantly addressed in the literature. Vocational exclusion affects deafblind individuals irrespective of age, financial status, education level, or place of residence. Promoting the employment of deafblind individuals in the open job market is linked to the policies of normalization, integration, and the acknowledgment of the rights of individuals with simultaneous hearing and visual impairments. The article highlights the need for changes in the support model for deafblind individuals in the job market. Special attention is paid to the employment barriers these individuals face, as well as an analysis of their strengths and weaknesses as employees.